Identification and characterization of the Onchocerca volvulus Excretory Secretory Product Ov28CRP, a putative GM2 activator protein. - Ferdinand Ngale Njume; Stephen Mbigha Ghogomu; Robert Adamu Shey; Lea Olive Tchouate Gainkam; Philippe Poelvoorde; Perrine Humblet; Joseph Kamgno; Annie Robert; Leon Mutesa; Christophe Lelubre; Evelina Edelweiss; Arnaud Poterszman; et al. (Public Library of Science (PLoS), 2019)
Onchocerca volvulus is the nematode pathogen responsible for human onchocerciasis also known as "River blindness", a neglected tropical disease that affects up to 18 million people worldwide. Helminths Excretory Secretory Products (ESPs) constitute a rich repertoire of molecules that can be exploited for host-parasite relationship, diagnosis and vaccine studies. Here, we report, using a range of molecular techniques including PCR, western blot, recombinant DNA technology, ELISA, high performance thin-layer chromatography and mass spectrometry that the 28 KDa cysteine-rich protein (Ov28CRP) is a reliable component of the O. volvulus ESPs to address the biology of this parasite. We showed that (1) Ov28CRP is a putative ganglioside GM2 Activator Protein (GM2AP) conserved in nematode; (2) OvGM2AP gene is transcriptionally activated in all investigated stages of the parasitic life cycle, including larval and adult stages; (3) The full-length OvGM2AP was detected in in-vitro O. volvulus ESPs of adult and larval stages; (4) the mass expressed and purified recombinant OvGM2AP purified from insect cell culture medium was found to be glycosylated at asparagine 173 and lacked N-terminal signal peptide sequence; (5) the recombinant OvGM2AP discriminated serum samples of infected and uninfected individuals; (6) OvGM2AP competitively inhibits MUG degradation by recombinant β-hexosaminidase A but not MUGS, and could not hydrolyze the GM2 to GM3; (7) humoral immune responses to the recombinant OvGM2AP revealed a negative correlation with ivermectin treatment. Altogether, our findings suggest for the first time that OvGM2AP is an antigenic molecule whose biochemical and immunological features are important to gain more insight into our understanding of host-parasite relationship, as well as its function in parasite development at large.